2019
DOI: 10.1371/journal.pone.0218332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of iron-reduced and iron-supplemented semisynthetic diets in T cell transfer colitis

Abstract: Clinical observations in inflammatory bowel disease patients and experimental studies in rodents suggest that iron in the intestinal lumen derived from iron-rich food or oral iron supplementation could exacerbate inflammation and that iron depletion from the diet could be protective. To test the hypothesis that dietary iron reduction is protective against colitis development, the impact of iron reduction in the diet below 10 mg/kg on the course of CD4+ CD62L+ T cell transfer colitis was investigated in adult C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Mice were fed with low (<9 mg elementary Fe/kg) ( 26 ) or high iron (5 g/kg) diets for two weeks and during the course of the infection. After intraperitoneal infection with 500 CFU of S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were fed with low (<9 mg elementary Fe/kg) ( 26 ) or high iron (5 g/kg) diets for two weeks and during the course of the infection. After intraperitoneal infection with 500 CFU of S .…”
Section: Resultsmentioning
confidence: 99%
“…For the infection model male mice were fed with different iron diets for two weeks and during the course of the infection. Low iron diet had an iron content of ≤9 mg iron/kg diet (26), high ion diet contained 5 g iron/kg diet (both diets from Altromin). Male mice were used at 8-12 weeks of age and infected intraperitoneally with 500 CFU of S. Typhimurium in 200 ml PBS (27)(28)(29).…”
Section: Infection Of Micementioning
confidence: 99%
“…Other hypotheses regarding the effects of chronic iron ingestion may be issued. Indeed, it was reported that iron is involved in the growth and function of immune cells and could modulate the Th1/Th2 ratio by a ROS-mediated mechanism [48,49,50], but contradictory results were found in different studies, possibly due to the form of iron [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…[ 125 ] In addition, as second messengers in cell signaling, excess ROS activate the NF‐κB signaling pathway and promote inflammatory cytokine generation. [ 126 ] Therefore, based on the intrinsic ROS‐scavenging properties of nanomaterials, antioxidant therapy is a reasonable and potential strategy for alleviating the development of atherosclerosis.…”
Section: The Targeting Strategies For the Therapy Of Vulnerable Ather...mentioning
confidence: 99%